Linker length and fusion site composition improve the optical signal of genetically encoded fluorescent voltage sensors - 정아롱; Jessica E. Garcia; Kim, Eun Ha; 윤봉준; Bradley Baker (SPIE, 2015)
Several genetically encoded fluorescent sensors of voltage were created by systematically truncating the length of the linker sequence between the voltage-sensing domain and the position of the fluorescent protein, Super Ecliptic A227D. In addition to varying the length, the amino acid composition at the fusion site for the fluorescent protein was modified. Both linker length and amino acid composition affected the size and voltage sensitivity of the optical signal. The truncation mutants revealed a potential structural periodicity with a maximum signal three amino acids from the voltage-sensing domain and another maximum 11 amino acids from the voltage-sensing domain. These results confirm that the linker length and composition can fine tune the size and voltage range of the sensor. The potential periodicity suggests that the orientation of the fluorescent protein could be important for improving the signal size implicating dimerization of the fluorescent protein.